Information support in social management: issues of improvement (Journal of Philosophy Culture and Political Science, 2018)
Information circulating in society is a very complex structure, comparable to complexity in society. In the last decade, the concept of “information” has been one of the most disputable. Considered applicable category formodern scientific ideas.